2015 IEEE International Conference on Control System, Computing and Engineering (ICCSCE) 2015
DOI: 10.1109/iccsce.2015.7482217
|View full text |Cite
|
Sign up to set email alerts
|

Computer vision-based hand deviation exercise for rehabilitation

Abstract: Computerized monitoring of the home based rehabilitation exercise has many benefits and it has attracted considerable interest among the computer vision community. Nowadays, many rehabilitation systems are proposed, most of the targeted disability is for stroke patient. Some of patient or user just wants to take certain part for rehabilitation. Therefore, this paper is focusing on hand rehabilitation system. The importance of the rehabilitation system is to implement the specific exercise for the specific requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It is studied that hand manipulation exercises can promote local motor enhancement, effectively enhancing muscle strength, flexibility, and coordination, while reducing discomfort related to prolonged use of electronic devices. In an existing study, Shuo Jiang demonstrated that repetitive exercise is the best strategy for restoring muscle activation, enhancing muscle strength, and avoiding hand fatigue [8].…”
Section: Hand Rehabilitation Movementsmentioning
confidence: 99%
“…It is studied that hand manipulation exercises can promote local motor enhancement, effectively enhancing muscle strength, flexibility, and coordination, while reducing discomfort related to prolonged use of electronic devices. In an existing study, Shuo Jiang demonstrated that repetitive exercise is the best strategy for restoring muscle activation, enhancing muscle strength, and avoiding hand fatigue [8].…”
Section: Hand Rehabilitation Movementsmentioning
confidence: 99%
“…These methods need only low-cost equipment that is easy to set up to monitor the human body. However, without control over specific conditions such as illumination and shadows, their detection accuracy may be reduced [10][11][12][13]. If the distance between the camera and an individual is inappropriate, the image information might be distorted owing to motion blur [14].…”
Section: Introductionmentioning
confidence: 99%
“…Based on non-wearable sensors, there are two main popular classes of methods in computer vision for detecting people in an image [10][11][12][13][14][15]. The methods in the first class are referred to as traditional methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation